2022
DOI: 10.1038/s41598-022-24593-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine modulation by etanercept ameliorates metabolic syndrome and its related complications induced in rats administered a high-fat high-fructose diet

Abstract: The aim of the present study was to investigate the effect of etanercept (ETA)—an anti-tumor necrosis factor α (TNF-α) monoclonal antibody—on metabolic disorders such as obesity, hypertension, dyslipidemia, and insulin resistance associated with the metabolic syndrome (MS). MS was induced in rats via high-fat high-fructose (HFHF) administration for 8 weeks. Rats were divided into three groups: negative control, HFHF model, and ETA-treated groups [HFHF + ETA (0.8 mg/kg/twice weekly, subcutaneously) administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…TNFα deficiency curtailed atherosclerotic lesion formation, possibly through attenuating macrophage foam cell formation and deposition in the arterial wall intima [46][47][48][49].Anti-TNFα antibody treatment restored the impaired coronary artery dilation in Db/Db mice through dampening NFkB (nuclear factor kappa B) mediated proinflammatory signaling [50]. Additional studies showed that Anti-TNFα ameliorated hypertension induced by a high-fat high-fructose diet in rat [51]. Subsequent mechanistic studies revealed that TNFα impaired the production of NO (nitro oxide) production and increased superoxide generation through NADPH oxidase in various vascular beds [48,52,53].…”
Section: Introductionmentioning
confidence: 98%
“…TNFα deficiency curtailed atherosclerotic lesion formation, possibly through attenuating macrophage foam cell formation and deposition in the arterial wall intima [46][47][48][49].Anti-TNFα antibody treatment restored the impaired coronary artery dilation in Db/Db mice through dampening NFkB (nuclear factor kappa B) mediated proinflammatory signaling [50]. Additional studies showed that Anti-TNFα ameliorated hypertension induced by a high-fat high-fructose diet in rat [51]. Subsequent mechanistic studies revealed that TNFα impaired the production of NO (nitro oxide) production and increased superoxide generation through NADPH oxidase in various vascular beds [48,52,53].…”
Section: Introductionmentioning
confidence: 98%